Designing a Mobile Health Solution to Facilitate the Transition from NICU to Home: A Qualitative Study - Ashwini Lakshmanan; Isabel Sunshine; Sam Calvetti; Juan Espinoza; Sofia Santoro; Saloni Butala; Madison House; Michele Kipke (MDPI AG, 2022)
There is limited information about caregiver and provider perspectives regarding the design of a mobile health solution to facilitate the transition from the neonatal intensive care unit (NICU) to home. Focus groups were conducted with English- or Spanish-speaking families enrolled in an urban high-risk infant follow-up clinic and with their care providers. We generated salient themes using an inductive thematic analysis. Twenty-two participants completed the study. Among caregivers, the infant's median gestational age (IQR) was 29 (23, 34) weeks and 63% were Hispanic. Among the providers, 55% had practiced for more than 10 years and 18% were bilingual. Key stakeholder (family and provider) priorities for designing a mobile health solution were organized into eight domains, i.e., implementation ideas around user interface and timing, providing path planning and information, increasing support, improving engagement with providers and services, mitigating barriers to care after discharge and strengthening parenting role and confidence. The results from this study suggest that families and healthcare providers prioritize path planning, information and support as the pillars for designing an effective NICU-to-home transition mobile health application. Implications for product development include family empowerment, being a credible source of information and creating a resource for caregiver support and mental health.